Internal Party Democracy and Institutionalization of Political Parties in Nigeria's Fourth Republic - Innocent, Alfa Patrick; Eikojonwa, Otaida; Yusoff , Kamarul Zaman Haji (South Asian Journal of Social Sciences and Humanities, 2020)
This paper interrogates the connection between the level of internal party democracy which exists in  Nigeria's Fourth Republic political parties and their propensity to become institutionalised. The  objective is to unravel the reason for their inability to make effective contribution the deepening of  democracy in the country. The paper is descriptive and conceptual. It got insights from secondary  data which includes journal articles, national dailies, internet, magazines and textbooks. The data  gathered were analysed under various themes. The paper contends that Nigeria's Fourth Republic  political parties do not adhere to the tenets of internal party democracy, thus undermining the  prospects of their institutionalisation and negates the performance of their democratic functions. The  paper offers valuable suggestions that could enhance the level of internal party democracy in the  parties, propel them towards institutionalisation and most fundamentally contribute optimally to the  consolidation of democracy in the Fourth Republic and beyond.
Keywords: Internal party democracy; political parties; Democratic consolidation; Fourth Republic; Nigeria